Topology Optimization of Gripping Jaws of Industrial Robot - Cedzo, Miroslav; Joch, Richard; Timko, Pavol; Holubjak, Jozef; Czanova, Tatiana; Sajgalik, Michal (Manufacturing Technology Journal, 2023)
There is a lot of applications for manipulating industrial robots nowadays. Maximizing the tasks that can be assigned to robot manipulators is one of the criteria for deciding if their application is appropri-ate. The article discusses the topology optimization of the gripping jaws of an industrial robot to reduce the jaws' weight. The previously used gripping element made of C50E steel was optimized to reduce the weight of the jaws. Shape optimization was performed based on analysis from CAD programs Inventor Professional 2022, Autodesk Fusion 360, and Ansys Discovery. The new jaws were manufactured by the additive technology of selective laser sintering (SLS) from PA12 material. The optimization resulted in a significant reduction in weight compared to the original jaws. As a result of optimizing the weight of the designed jaws, it was possible to increase the weight of the object of manipulation.
Keywords: Topology Optimization; Gripping Jaws; Additive Manufacturing; SLS; Generative Design